Peripheral neuropathy associated with essential mixed cryoglobulinaemia: a role for hepatitis C virus infection?. Issue 6 (June 1996) - Apartis, E; Léger, J M; Musset, L; Gugenheim, M; Cacoub, P; Lyon-Caen, O; Pierrot-Deseilligny, C; Hauw, J J; Bouche, P
Abstract : BACKGROUND--The prevalence of hepatitis C virus (HCV) infection has been estimated at 43 to 84% in patients with essential mixed cryoglobulinaemia in recent large series. Some of these cases have been successfully treated with interferon-alpha. The objective was to evaluate the prevalence and the possible role of HCV infection in essential mixed cryoglobulinaemia. METHODS--Fifteen patients (eight men and seven women; mean age: 61.2 (SD 16.5) years) with peripheral neuropathy (10 polyneuropathies and five multifocal mononeuropathies) and essential mixed cryoglobulinaemia were tested for serum anti-HCV antibodies. RESULTS--Antibodies were found in 10 of 15 patients involving either polyneuropathies (seven patients) or multifocal mononeuropathies (three patients). Electrophysiological studies and teased nerve fibre studies (in seven patients) allowed neuropathies to be classified as predominantly sensory axonopathies. Compared with HCV-negative (HCV -) patients, HCV-positive (HCV +) patients had a more pronounced and more widespread motor deficit; motor nerve conduction velocities in peroneal and median nerves were more impaired in HCV + patients, although significance was not reached except for the mean value of the amplitude of the compound muscle action potentials of the median nerves (P < 0.05); necrotising vasculitis was found in two of nine nerve biopsies from the HCV + patients studied and in none of the three HCV - patients. In addition, HCV + patients had more frequent cryoglobulin related cutaneous signs, higher aminotransferase and serum cryoglobulin concentrations, lower total haemolytic complement concentrations, and more frequent presence of rheumatoid factor. A liver biopsy performed in eight HCV + patients disclosed a range of lesions, from chronic active hepatitis (six patients) to persistent hepatitis (two patients). Lastly, treatment with interferon-alpha conducted over six months in two patients seemed to improve the peripheral neuropathy. CONCLUSIONS--Patients with peripheral neuropathy and essential mixed cryoglobulinaemia should be tested for anti-HCV antibodies to determine the appropriate treatment.